Graphitized Mesoporous Carbon Derived from ZIF-8 for Suppressing Sulfation in Lead Acid Battery and Dendritic Lithium Formation in Lithium Ion Battery. Issue 13 (1st January 2018) - Xu, XiaoLong; Wang, Hao; Xie, YiZhu; Liu, JingBing; Yan, Hui; Liu, Wei
Abstract : Electrode stability has been an important parameter in energy conversion and storage devices. However, many of these electrodes suffer from irreversible degradation, for example, irreversible sulfation in the negative electrode of lead acid battery (LAB) and lithium dendrite on the anode surface of lithium ion battery (LIB). We here report a facile synthesis approach of graphitized mesoporous carbons (GMCs), which derived from zeolitic imidazolate frameworks-8 (ZIF-8) via controlling the annealing parameters, as porous media in the electrodes for suppressing the irreversible sulfation and the dendritic lithium formation. GMC additive in the negative electrode of LAB effectively retards the irreversible sulfation by controlling the growing size of PbSO4 crystal particles. The cycle life of LAB extends 8.5 times after being added GMC additive. Dendrite growth in LIBs is suppressed obviously because GMCs control the lithium growth along the mesoporous structure and the particle voids of GMCs, resulting in the significant extension of operation time of the LIB without a short circuit. The capacity retention of Li and Li/GMC anodes are 42.3% and 90.1%, respectively, at 0.5 C after 200 cycles. The work reveals a facile but efficient synthesis approach of additive to extend the cycle life of LABs and LIBs.